Post Circumcision Intraperitoneal Rupture of the Urinary Bladder: A Rare Complication - Sherif Abdelmaksoud; Mohammed Albishbishy; Mostafa Elayyouti; Mohamed Zohiri; Adham Elsaied (Georg Thieme Verlag KG, 2020)
Circumcision is one of the most common pediatric surgical procedures performed all over the world and especially in Arab and Islamic countries. Many complications have been documented following this maneuver. We report on a rare case of intraperitoneal bladder rupture in a 7-day-old baby who was circumcised on his second day using the guillotine method. He presented to us with gangrene of the tip of the penis and a failure to void urine associated with progressive abdominal distension. Ultrasound revealed severe ascites. Aspiration and analysis confirmed the fluid to be urine. Ascending cystourethrogram was performed revealing a perforation of the posterior bladder wall near the trigone. Exploration was performed and repair done. Postoperative course was uneventful.